60 years of the Antarctic Treaty – history and celebration in radio waves - V. Strecke; V. Strecke (Polarforschung, 2022)
The Antarctic Treaty, successfully negotiated and signed in 1959, entered into force after ratification by the 12 original signatory countries in 1961. Under the Antarctic Treaty, research activities are now carried out in Antarctica by 54 countries. These are 29 consultative and 25 non-consultative parties. Radio communications have always been an important part of all scientific activities in research stations, ships and aircraft in Antarctica. Historic expeditions in the 19th century and early 20th century had to use wired telegraph stations after returning from expeditions. Between 1911 and 1913, Wilhelm Filchner and Douglas Mawson were the first Antarctic expedition leaders to explore the possibilities of wireless telegraphy. Mawson succeeded in establishing radio communications from Antarctica to Australia for the first time in 1912. Today, the use of communication technologies is almost taken for granted. Direct amateur radio communications via shortwave are a flexible backup and an effective addition to communications about the Antarctic. On the occasion of the 60th anniversary of the Antarctic Treaty, a major international radio activity was launched in the second half of 2021 with which an important contribution to communication to the public was made. Amateur radio is now an important part of research activities in Antarctica.